Mountains Mysteries: Unraveling the Mystical Allure of Mount Everest and Mount Annapurna - Gautam, Pragya (Journal of Tourism and Himalayan Adventures, 2024)
This article explores the mysterious and mystical allure of Mount Everest and Mount Annapurna, delving into the rich tapestry of cultural, religious, and historical narratives associated with these towering peaks. Drawing upon the perspectives of geographers, mountaineers, and authors, the article navigates the spiritual significance of high–altitude mountains like Mount Everest and Mount Annapurna, and the captivating legends of mythical beings like Yeti. The narrative unfolds with a vivid portrayal of the sacredness attributed to the Himalayan region, emphasizing the belief in deities and spirits inhabiting these majestic peaks. It also sheds light on the transformative experiences of climbers who, despite acknowledging the risks and challenges, find liberation, joy, and a profound connection with nature upon reaching the summit. The article concludes by highlighting the unparalleled beauty of the Himalayas, drawing on the accounts of climbers and authors who describe the sublime landscapes, pristine environments, and the spiritual resonance that makes these mountains a timeless source of inspiration and fascination.